2015
DOI: 10.1371/journal.pone.0123795
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue Activation Is Inversely Related to Central Obesity and Metabolic Parameters in Adult Human

Abstract: BackgroundRecent studies have shown that adult human possess active brown adipose tissue (BAT), which might be important in affecting obesity. However, the supporting evidence on the relationship between BAT and central obesity and metabolic profile in large population based studies is sparse.Methodology/Principal FindingsWe studied 4011 (2688 males and 1323 females) tumor-free Chinese adults aged 18-89 for BAT activities, visceral/subcutaneous fat areas (VFA/SFA), waist circumferences (WC) and metabolic param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 53 publications
7
78
1
3
Order By: Relevance
“…Interestingly, a potential solution to the problem of obesity-associated diseases has been found in brown fat, a type of adipose tissue that dissipates energy through a thermogenesis process. Previous studies showed that activated BAT is inversely correlated with BMI [65] , adipose tissue mass and insulin resistance. Thus, BAT is one of the best targets for creating strategies to treat obesity and obesity-associated diseases.…”
Section: Resultsmentioning
confidence: 96%
“…Interestingly, a potential solution to the problem of obesity-associated diseases has been found in brown fat, a type of adipose tissue that dissipates energy through a thermogenesis process. Previous studies showed that activated BAT is inversely correlated with BMI [65] , adipose tissue mass and insulin resistance. Thus, BAT is one of the best targets for creating strategies to treat obesity and obesity-associated diseases.…”
Section: Resultsmentioning
confidence: 96%
“…6,[13][14][15][16][17]19,21 BAT activity was found to be higher in women, in many oncology studies. [13][14][15][16][17]20 However, no sex differences were found in 18 FDG-PET∕CT studies with cold exposure. 6,22 The oncology studies had very large sample sizes but did not include cold exposure, whereas the studies using 18 FDG-PET∕CT with cold exposure had relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 94%
“…We showed that body fatness parameters were negatively correlated with BAT-d, which is consistent with the results of various studies that used 18 FDG-PET∕CT, regardless of the presence of cold exposure. 6,[14][15][16][17]19,20 Although we should consider the possibility that the BAT-d was affected by subcutaneous fat thickness, 26 the subcutaneous fat thickness in the supraclavicular region is within a very narrow range and has little effect on the measured parameters. For instance, the fat thickness in the supraclavicular region ranged from 0.6 to 2.5 mm when evaluated by B-mode ultrasonography in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). However, the amount of detectable active BAT in humans varies depending on age, body mass and season Wang et al, 2015), and shows higher prevalence in young, lean women than in men .…”
Section: Adipose Tissue Depotsmentioning
confidence: 99%